Historical land use dataset of the Carpathian region (1819-1980) - Juraj Lieskovský; Dominik Kaim; Pál Balázs; Martin Boltižiar; Mateusz Chmiel; Ewa Grabska; Géza Király; Éva Konkoly-Gyuró; Jacek Kozak; Katarína Antalová; Tetyana Kuchma; Peter Mackovčin; et al. (Journal of Maps, 2018)
We produced the first spatially explicit, cross-border, digital map of long-term (160 years) land use in the Carpathian Ecoregion, the Hungarian part of the Pannonian plains and the historical region of Moravia in the Czech Republic. We mapped land use in a regular 20.167em0.167em20.25emkm point grid. Our dataset comprises of 91,310 points covering 365,2400.25emkm² in seven countries (Czechia, Slovakia, Austria, Hungary, Poland, Ukraine and Romania). We digitized three time layers: (1) for the Habsburg period, we used maps of the second Habsburg military survey from years 1819–1873 at the scale 1:28,800 and the Szatmari's maps from years 1855–1858 at scale 1:57,600; (2) The World Wars period was covered by national topographic maps from years 1915–1945 and scales here ranged between 1:20,000–1:100,000; and (3) the Socialist period was mapped from national topographic maps for the years 1950–1983 at scales between 1:25,000–1:50,000. We collected metadata about the years of mapping and map sources. We used a hierarchical legend for our maps, so that the land use classification for the entire region consisted of 9 categories at the most general level and of 22 categories depending on the period and a country.
http://doi.org/10.6084/m9.figshare.7234676.v1
Keywords: 330; landscape history; land use change; historic maps; military topographic maps; forest; agriculture; grasslands